Grassland management effects on biodiversity and ecosystem functioning grassland management effects on biodiversity and ecosystem functioning - Furquim, Fernando Forster (2023)
Grasslands worldwide occupy approximately 40% of Earth terrestrial surface and are habitat for large biodiversity and provider of ecosystem functions, being fire and grazing the key drivers of grassland biodiversity and ecosystem. Despite it, grasslands are one of the most converted ecosystems worldwide, wherein different vegetation management to raise herds lead to changes on plant species composition and ecosystem functioning. Three articles composed this thesis in order to elucidate how these changes are driven by different land uses from livestock perspective. We assessed how plant species composition differs in terms of plant species composition, richness, and ecosystem functions by comparing (i) natural grasslands and cultivated pastures from North and South America; (ii) natural grasslands grazed and ungrazed for 8 eights in Río de la Plata grasslands region (RPG); and (iii) different fire treatments, including fire and grazing interaction, in subtropical grasslands from southern Brazil. Our results showed clear differences among treatments from all chapters, wherein mainly findings showed that (i) conversion of natural grasslands into cultivated pastures, and large grazers exclusion lead to reduced root biomass and higher arthropods herbivory damage, which may increase, respectively, risk to adverse climatic events (e.g. drought) and pest infestation; (ii) reduction on plant species richness in cultivated pastures and in ungrazed areas in comparison to, respectively, natural grasslands and grazed areas from RPG; and (iii) disruption of biotic interactions by reduction on lepidopterans and coleopterans abundances as floral visitors in cultivated pastures. Furthermore, our findings regarding different fire treatments showed the potential of prescribed fires to reduce and increase, respectively, shrubs and C3 grasses coverages while maintaining plant species richness, indicating its use as vegetation management tool in grazing systems.